Testing and numerical modelling of austenitic stainless steel CHS beam–columns. (15th March 2016) - Zhao, Ou; Gardner, Leroy; Young, Ben
Highlights: 12 austenitic stainless steel CHS beam–column tests have been carried. FE models have been validated against tests and used to perform parametric studies. Design provisions in EC3, SEI/ASCE and AS/NZS have been described and discussed. The applicability of each approach has been assessed against test and FE results. The weakness of the current design approaches has been highlighted. Abstract: This paper presents a comprehensive experimental and numerical study of the global stability of stainless steel circular hollow section (CHS) structural members subjected to combined axial load and bending moment. The experimental investigation, which was carried out on two grade 1.4301 austenitic stainless steel cross-section sizes (CHS 60.5 × 2.8 and CHS 76.3 × 3), included material coupon tests, initial geometric measurements, two column tests, and ten beam–column tests. The test results were employed in a parallel numerical simulation programme for the validation of finite element (FE) models, by means of which a series of parametric studies were carried out to extend the available results over a wider range of cross-section sizes, member lengths and loading combinations. The experimentally and numerically derived data were used to assess the structural performance of CHS beam–columns and to determine the accuracy of the current design provisions given in the European code, American specification, Australian/New Zealand standard, and other recent proposed approaches. Generally, all the existing design methods were shown to yield a high degree of scatter in the prediction of beam–column strength, with both conservative and over-predicted capacities. The scatter was attributed mainly to inaccurate predictions of the column buckling and bending end points of the design beam–column interaction curves (i.e. member strengths under pure compression and pure bending, respectively) and inaccurate interaction factors. The development of improved provisions for the design of stainless steel circular hollow section beam–columns is currently underway.